Efficacy of Soil Conditioners and Nitrogen under Saline-sodic Irrigation on Sugarbeet (Beta vulgaris L.) Dry Matter, Yield and Sugar Production - Totawat, K L; Singh, R M (Annals of Arid Zone, 2016)
Results of an experiment conducted for two consecutive years (1970-71 and 1971-72) at Jobner (Rajasthan) show that sugarbeet crop can be grown successfully in light textured soil with a saline sodic water of EC 4 mmhos. Incorporation of soil conditioners like sulphur, gypsum or cowdung to the soil increased the dry matter production throughout the growth period and yield of fresh root, green leaf and projected sugar. There is a linear increase with increase in nitrogen level in root yield upto 60 kg/ha and in projected sugar yield upto 60 kg/ha of nitrogen applied.